Determinación de especies de Flora como fuente de bioconocimiento ancestral en la parroquia Chugchilán cantón Sigchos Provincia de Cotopaxi - Banda Vilca, Erika Estefania (2017)
The objective of this research was to determine flora species in six indigenous communities at Chugchilán Parish, Sigchos Canton, Cotopaxi Province, considering the diversity of flora in that area, thus obtaining information about the usefulness and traditional management of vegetable species. In recent years, ethnobotanical studies have become very important because it refers to the relationship between people and plants to satisfy each of their common needs without having to acquire conventional drugs or processed products. To carry out the project, those agricultural producers: seniors, shamans, healers, midwives, among others were visited due to they well know the benefits of plants, and by using the direct observation and field sheet were collected information of the vegetable species in each communities. The research had the help of a guide from the study area, the results obtained in the project were that the significant presence of flora species is the Asteraceae family with 16%. The research contributes to the recovery of ancestral knowledge in the process of disappearing; it was possible to register the ancestral knowledge of the plant species of the Chugchilán Parish which final result was a catalog.